Addressing the need for safe, nutritious and sustainable food: Outcomes of the "ONE – Health, Environment & Society – Conference 2022″. (November 2022) - Devos, Yann; Arena, Maria; Ashe, Sean; Blanck, Max; Bray, Edward; Broglia, Alessandro; Bronzwaer, Stef; Cafaro, Angelo; Corsini, Elisa; Dujardin, Bruno; Dumont, Antonio Fernandez; Garcia, Matilde Gomez; et al.
Abstract: Background: On 21–24 June 2022, the European Food Safety Authority, together with the European Centre for Disease Prevention and Control, the European Chemicals Agency, the European Environment Agency, the European Medicines Agency, and the Joint Research Centre of the European Commission, held the "ONE – Health, Environment & Society – Conference 2022". Scope and approach: The conference brought together experts and stakeholders to reflect on how scientific advice related to food safety and nutrition will need to develop to respond to a fast-changing world. The event also explored how institutions that provide such advice should best prepare for the challenges ahead, and how they can contribute to policy targets and societal demands for safe, nutritious and sustainable food. Key findings and conclusions: Overall, participants concluded that food safety assessments must be further advanced to remain fit for purpose and increase their relevance to society. To address the growing complexity in science and society, new ways of working that connect and integrate knowledge, data and expertise across a wide range of disciplines, sectors and actors must be embraced. One Health provides a valuable conceptual framework for advancing food safety assessments by ensuring the delivery of more integrated, cross-sectoral and collaborative health assessments. These assessments may help to better inform policies that support the transition towards a sustainable food system. As such, One Health could serve as a steppingstone to sustainable food. Urgent action is now required to define how the One Health principles can be implemented in food safety and nutrition. Highlights: Safe food is the basis for healthy diets and sustainable food systems. New ways of working are needed to advance food safety assessments. Such assessments require cross-sectoral cooperation and more integrated approaches. Actions are recommended to build a collaborative ecosystem of food safety actors. One Health can support the transition to safe, nutritious and sustainable food.